Clinicopathologic Characteristics and Patient Outcomes of Phyllodes Tumors: A Single Institution Experience. Issue 10 (October 2021) - Mohan, Srivarshini Cherukupalli; Tseng, Joshua; Angarita, Stephanie; Marumoto, Ashley; Dadmanesh, Farnaz; Amersi, Farin; Giuliano, Armando; Chung, Alice
Phyllodes tumors (PT) are rare fibroepithelial neoplasms that are classified as benign, borderline, or malignant. Patients with PT diagnosed between 2009 and 2019 were identified from a prospectively maintained single institutional database. 76 patients with PT were included; 47 (61.8%) were benign, 9 (11.8%) were borderline, and 20 (26.3%) were malignant. The mean age at diagnosis was 52. Surgical treatment of benign PT included excisional biopsy in 31 (66.0%) patients, segmental mastectomy in 15 (31.9%), and mastectomy in 1 (2.1%). Among patients with borderline PT, operative management was excisional biopsy in 4 (44.4%) and segmental mastectomy in 5 (55.6%). Of those with malignant PT, 7 (35.0%) were treated with excisional biopsy alone, 9 (45.0%) had lumpectomy (segmental mastectomy), and 4 (20.0%) underwent mastectomy. Malignant PT had a higher rate of necrosis compared to borderline or benign PT (25.0% vs 0% vs 4.3%, P = .016). Four patients had recurrent PT. Final positive margins were associated with recurrence ( P = .044). The median overall follow-up time was 86.3 months (range 1.5-1414.1 months), and no deaths occurred among patients with malignant PT. Overall, recurrence rates of PT are low but may be increased by presence of positive margins.